1990
DOI: 10.1093/nar/18.7.1825
|View full text |Cite
|
Sign up to set email alerts
|

The primary structure and expression of the second open reading frame of the polymerase gene of the coronavirus MHV-A59; a highly conserved polymerase is expressed by an efficient ribosomal frameshifting mechanism

Abstract: Sequence analysis of a substantial part of the polymerase gene of the murine coronavirus MHV-A59 revealed the 3' end of an open reading frame (ORF1a) overlapping with a large ORF (ORF1b; 2733 amino acids) which covers the 3' half of the polymerase gene. The expression of ORF1b occurs by a ribosomal frameshifting mechanism since the ORF1a/ORF1b overlapping nucleotide sequence is capable of inducing ribosomal frameshifting in vitro as well as in vivo. A stem-loop structure and a pseudoknot are predicted in the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
174
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(179 citation statements)
references
References 46 publications
5
174
0
Order By: Relevance
“…Apparently the ratio between the levels of ORF 1 a-and ORF 1 b-derived proteins in infected cells has to be regulated. Using reporter gene constructs, frameshifting efficiencies in expression systems of 25 to 40 %, 20 to 30 % and 15 to 20 % have been observed for corona-, toro-and arteriviruses, respectively (Brierley et al, 1989;Bredenbeek et al, 1990a;Snijder et al, 1990a;den Boon et al, 1991b).…”
Section: The 'Coronavirus-like' Replicasementioning
confidence: 99%
“…Apparently the ratio between the levels of ORF 1 a-and ORF 1 b-derived proteins in infected cells has to be regulated. Using reporter gene constructs, frameshifting efficiencies in expression systems of 25 to 40 %, 20 to 30 % and 15 to 20 % have been observed for corona-, toro-and arteriviruses, respectively (Brierley et al, 1989;Bredenbeek et al, 1990a;Snijder et al, 1990a;den Boon et al, 1991b).…”
Section: The 'Coronavirus-like' Replicasementioning
confidence: 99%
“…The second open reading frame ORF1b, overlaps ORF1a for 75 nucleotides and is 2771 amino acids long. In vitro transcription and translation studies of gene 1 have indicated that these two ORFs are translated by a ribosomal frameshifting mechanism to yield a polyprotein of almost 800 000 kDa which is co-translationally cleaved (Breedenbeek et al, 1990). Analysis of the nucleotide sequence and the predicted amino acid sequence revealed that ORF1a contains several likely functional domains: two hydrophobic domains, three cysteine-rich domains, a picornavirus 3C-like protease domain, and two papain-like protease domains (Lee et al, 1989;Bonilla et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The relative positions of these ORF1a domains are depicted schematically in Figure 1. ORF1b is predicted to encode domains required for the MHV RNA-dependent RNA polymerase activity, including the canonical SDD polymerase motif, a nucleotide binding motif, a metal binding domain, and a helicase domain (Breedenbeek et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…The unique region of MHV mRNA 1 contains two large ORFs that constitute the coronavirus RNA polymerase locus. Expression of viral proteins from this locus involves both ribosomal frameshifting and autoproteolytic processing (Baker et al, 1989;Bredenbeek et al, 1990;Denison et al, 1991Denison et al, , 1992. MHV mRNA 5 also contains two ORFs in its unique region, designated ORF 5a and ORF 5b.…”
Section: Introductionmentioning
confidence: 99%